PENGARUH GAYA KEPEMIMPINAN PENGURUS TERHADAP PARTISIPASI ANGGOTA KOPERASI SUKA DAMAI DESA KEPENUHAN SEI MANDIAN KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU - Dhini Gusshandri Darni; Caska '; Syakdanur Nas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to determine the effect of Leadership Style Cooperative Board Member Participation Against Suka Damai Village Fullness Fullness of Rokan Hulu subdistrict . Research methods included in a correlation study . Population cooperative members as many as 485 people The sampling technique used is the technique slovin 83 people . for the dependent variable : the leadership style ( X ) ; independent variables : participation ( Y ) . The data analysis technique used is simple linear regression statistical techniques . From the results , it can be concluded that : ( 1 ) the influence of leadership style on the participation of members of the cooperative ; ( 2 ) the influence of leadership style on the participation of members of 48.9 % .Keywords : influence , leadership style , the participation of members.